2019
DOI: 10.1097/mao.0000000000002069
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Audiometric and Clinical Outcomes Following Stapedectomy With the Shape Memory Nitinol Stapes Prosthesis

Abstract: Objective: To assess long-term hearing outcomes following stapedectomy using a self-crimping shape memory nitinol prosthesis. The results were compared with those of a group of patients who received a conventional prosthesis. Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: All patients who underwent stapedectomy for otosclero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
2
2
0
Order By: Relevance
“…When considering only primary stapedotomies performed by surgeons at our institution in the last 20 years, we found a 4.49% revision rate. This is comparable to a recent study by Heywood et al ( 31 ), which demonstrated a revision rate of 4.5% in stapedotomies performed between 2001 and 2008 using the shape memory Nitinol prosthesis, as was employed in all procedures in our series. These numbers are in contrast to other large, historic case series that have demonstrated higher proportions of patients requiring revision stapedotomy, ranging from 2.6 to 29.4% ( 20 , 31 34 , 36 39 ).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…When considering only primary stapedotomies performed by surgeons at our institution in the last 20 years, we found a 4.49% revision rate. This is comparable to a recent study by Heywood et al ( 31 ), which demonstrated a revision rate of 4.5% in stapedotomies performed between 2001 and 2008 using the shape memory Nitinol prosthesis, as was employed in all procedures in our series. These numbers are in contrast to other large, historic case series that have demonstrated higher proportions of patients requiring revision stapedotomy, ranging from 2.6 to 29.4% ( 20 , 31 34 , 36 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…This is comparable to a recent study by Heywood et al ( 31 ), which demonstrated a revision rate of 4.5% in stapedotomies performed between 2001 and 2008 using the shape memory Nitinol prosthesis, as was employed in all procedures in our series. These numbers are in contrast to other large, historic case series that have demonstrated higher proportions of patients requiring revision stapedotomy, ranging from 2.6 to 29.4% ( 20 , 31 34 , 36 39 ). Interpretation of these numbers must be guarded, though, given the risks of: 1) revision surgeries being performed at longer intervals than those captured in our study, and 2) factors such as patient relocation, insurance coverage, or preferences leading them to undergo revision at institutions other than our own.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…To address that, prostheses that do not require crimping have been introduced, including the classic bucket handle prosthesis and its modifications. More recently, nitinol-based prostheses that assume a predetermined shape once heated, for example with bipolar cautery, CO 2 laser, or a heat applicator, have been introduced, and have been shown to be safe and effective (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%